The determinants of adolescent smokers in Indonesia - Novin Yetiani; Linda Suwarni; Heni Rusmitasari; Maretalinia Maretalinia; Sindu Setia Lucia; Suyitno Suyitno (International Journal of Public Health Science (IJPHS), 2022)
In Indonesia, the prevalence of adolescence smokers is high. The situation might be worse during the epidemiological transition. This study aimed to estimate the sociodemographic factors related to tobacco use (light, moderate, and heavy) among adolescent in school age in Indonesia. This cross-sectional study used the raw data from the secondary data of Indonesia Global Youth of Tobacco Survey (GYTS), 2019. This study only included the 9,992 adolescent smokers in school age as the sample. School was selected based on the proportional probability based on the number of students. The class was selected by random sampling method and the students in that class were eligible to join the survey. This current study only selected those who smoked at the time of survey. The univariate, bivariate (Chi-square and t-test), and multivariate (ordinal logistic regression) has been tested in this study. The prevalence of tobacco uses among adolescent in Indonesia in 2019 was 19.2%. The determinants of tobacco use mostly related to pocket money, having products with cigarettes logo, and can purchase near the school. The role of sociodemographic, factors related to current tobacco use is very important to arrange the policy. The policy is very important to prevent and control tobacco use, especially among adolescence.